Tinjauan Yuridis Terhadap Jual Beli Surat Keterangan Sakit Di Dunia Online (E-Commerce): Tinjauan Yuridis Terhadap Jual Beli Surat Keterangan Sakit - Yohanes Firmansyah; Yana Sylvana; Hanna Wijaya; Michelle Angelika S (Yayasan Pendidikan Medika Indonesia, 2021)
Often with the rapid development of technology and online commerce, especially e-commerce, it also has an impact on the increasing number of criminal incidents in electronic media. One of the criminal acts that occurs is the forgery of sick letters that doctors usually give to patients who need rest because of their illness. This paper discusses the criminal law aspects of the sale of fake sick letters via electronic media with a review of Law of the Republic of Indonesia Number 11 of 2008 concerning Electronic Information and Transactions, Article 378 of the Criminal Code, and Article 62 of the Consumer Protection Act.